Functional nuclear architecture studied by microscopy: present and future - Rouquette, Jacques; Cremer, Christoph; Cremer, Thomas; Fakan, Stanislav (International review of cell and molecular biology, 2010)
In this review we describe major contributions of light and electron microscopic approaches to the present understanding of functional nuclear architecture. The large gap of knowledge, which must still be bridged from the molecular level to the level of higher order structure, is emphasized by differences of currently discussed models of nuclear architecture. Molecular biological tools represent new means for the multicolor visualization of various nuclear components in living cells. New achievements offer the possibility to surpass the resolution limit of conventional light microscopy down to the nanometer scale and require improved bioinformatics tools able to handle the analysis of large amounts of data. In combination with the much higher resolution of electron microscopic methods, including ultrastructural cytochemistry, correlative microscopy of the same cells in their living and fixed state is the approach of choice to combine the advantages of different techniques. This will make possible future analyses of cell type- and species-specific differences of nuclear architecture in more detail and to put different models to critical tests.
Gesehen am 22.06.2023